Knockdown of HIF‐1α impairs post‐ischemic vascular reconstruction in the brain via deficient homing and sprouting bmEPCs. (9th October 2018) - Liu, Yang; Ran, He; Xiao, Yaping; Wang, Hongjin; Chen, Yi; Chen, Weihai; Xu, Xiaoyu
Abstract: Although the critical role of hypoxia inducible factor‐1α (HIF‐1α) in cerebral neovascularization after stroke has been well characterized, the details regarding the regulation of endothelial progenitor cell (EPC)‐dependent neovascularization by HIF‐1α are not completely understood. Using lentiviral shRNA to knockdown HIF‐1α, we showed that HIF‐1α plays a central role in bone marrow‐derived EPC (bmEPC) homing and sprouting in the post‐acute stage of ischemic Sprague Dawley (SD) rat brains. First, knockdown of HIF‐1α decreased the homing of both endogenous and exogenous bmEPCs to the ischemic brain. Additionally, the knockdown impaired the incorporation and sprouting of bmEPCs in the ischemic brain. In vitro, knockdown of HIF‐1α inhibited the spheroid sprouting and tube formation of bmEPCs. Mechanically, the HIF‐1α‐dependent recruitment of bmEPCs to the ischemic brain was relative to the CXCL12/CXCR4 axis and HMGB1, which were relative to astrocytes. In addition, the loss of HIF‐1α resulted in deficient expression levels of VEGF‐A, Flk‐1, NRP1, and Dll4 in the ischemic brains, bmEPCs, and astrocytes. These findings suggested that HIF‐1α implicates in bmEPC homing via CXCL12/CXCR4 and HMGB1 and that it promotes bmEPC sprouting via VEGF‐A/flk1‐NRP1/Dll4.